Thermo-Catalytic Reforming (TCR)–An important link between waste management and renewable fuels as part of the energy transition - Hornung, Andreas; Jahangiri, Hessam; Ouadi, Miloud; Kick, Christopher; Deinert, Lisa; Meyer, Benedikt; Grunwald, Jan; Daschner, Robert; Apfelbacher, Andreas; Meiller, Martin; Eder, Stefan (Applications in Energy and Combustion Science, 2022)
The significant progress in energy demands and limited fossil fuel sources, together with environmental concerns, have enforced the study of green, renewable, and sustainable energy sources. Biomass and its residues can be converted into valued fuels and chemicals through advanced thermal conversion technologies. Pyrolysis has been used for a long time for charcoal formation, while intermediate and fast pyrolysis technologies have become of considerable interest in recent years. This substantial interest is because these processes provide different bio-products (synthesis gas, bio-oil and biochar), which can be used directly in numerous applications or as a sustainable energy carrier. This paper investigates an overview of the fundamentals of Thermo-Catalytic Reforming (TCR) technology which is a novel intermediate pyrolysis process combined with a post catalytic reforming unit. This study also identifies the TCR process's features and advantages compared to other pyrolysis technologies, followed by a technical scale unit and the transfer of intermediates in final products. Finally, the treatment of effluents, heat management and implementation of such technologies are discussed. This paper shows how a continuous pyrolysis/reforming plant has been developed and established based on targeted reactor design and in conjunction with preventing major effluent streams, which could have a major impact on the technology's commercial success. Along with two major European projects (To-Syn-Fuel and GreenFlexJET), the TCR technology shall help to overcome the dependency on fossil crude oil and fuels.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Bioenergy; Hydrodeoxygenation; Pyrolysis; Thermo-Catalytic Reforming (TCR)